LINGUISTIC POLITENESS IN EXPRESSIVE SPEECH ACTS ON THE PODCAST 'CURHAT BANG DENNY SUMARGO - Tiara Sesmita; Juita, Novia (JURNAL KONFIKS, 2025)
Linguistic politeness in everyday conversations is crucial for maintaining social relationships. However, in the context of digital media, particularly podcasts, linguistic politeness is often overlooked or unnoticed. The podcast Curhat Bang Denny Sumargo has become one of the platforms that feature informal conversations with various verbal expressions that can influence the understanding of linguistic politeness. This study aims to analyze expressive speech acts in the podcast and examine how linguistic politeness is applied in conversations between guests with specific social relationships. The method used is a qualitative approach with a corpus linguistics approach, and data is obtained from transcripts of episodes selected through purposive sampling. Data collection was done by listening to and transcribing each selected episode, and then analyzing it using expressive speech act theory, speech strategies, and the politeness principles of Brown and Levinson. The research results show that linguistic politeness in this podcast is greatly influenced by the social context and the relationships between the guests, as well as the expressive expressions used in different communication situations. In conclusion, this study reveals that expressive speech acts in the podcast provide insights into the application of linguistic politeness in digital media, which is often more relaxed and informal compared to face-to-face conversations.